The Art of Monstrosity: Shannon’s Monstrous Body Transformation in Palahniuk’s Invisible Monster: - - Iftinan Rose Putri Safana -; Novi Siti Kussuji Indrastuti (Darussalam English Journal (DEJ), 2025)
The novel Invisible Monster by Chuck Palahniuk reflects the phenomenon of body transformation, such as mutilation, which is considered by society as a deviation from the norm and is called a monstrous body. The discourse is expressed through the character Shannon who carries out facial mutilation; thus, providing space to better understand the phenomenon as an effort to deconstruct established norms. This study aims to investigate the form and factors of monstrous body transformation. To achieve this goal, the researcher used a descriptive qualitative approach by applying two theories, namely Steinhoff's Body Transformation theory and Bakhtin's Grotesque Body theory. This study found a monstrous body form in the form of a crushed face, experienced by Shannon. The crushed face was because Shannon shot herself in the face. Therefore, Shannon's face was destroyed, her jaw was open, her tongue was sticking out, and she continued to bleed and ooze. The crushed face deviated greatly from society's norms of ideal beauty; thus, it was called a monstrous body. Then, this study identified the factors of Shannon's monstrous body transformation, namely abberanormia, which was developed from the Body Transformation theory. Abberanormia was identified from Shannon's condition of wanting to break the norms of beauty not because she was unable to meet them, but because she had reached those standards and felt bored.